Guidelines for molecular testing in non-small cell lung cancer - recommendations from the Brazilian Society of Pathology - Fabio Tavora; Clarissa Baldotto; Francisco Martins Neto; William William; Igor Campos Da Silva; Nicolle Cavalcante Gaglionone; Felipe D'Almeida; Emilio Assis (BMC, 2023)
Abstract The Brazilian Society of Pathology Guidelines project aims to provide recommendations for clinicians and pathologists based on the best available scientific evidence adapted from the International Guidelines, with emphasis in the practice of Brazilian pathologists. It reviews currently available and emerging molecular tests. In this paper, a combined effort from members of the Brazilian Society of Pathology describes the essential pre-analytical issues, the required clinical information to allow proper molecular testing interpretation, and the important role of pathologists in multidisciplinary tumor boards.